Система суб’єктів протидії нелегальній міграції в Україні та особливості їх адміністративно-правового статусу - Соколовський, А. С.; Sokolovskyi, A. S. (Право.ua. - 2024. - № 2. - С. 276-281, 2024)
Наголошено , що суб’єкт протидії нелегальній міграції в Україні - це фізична або юридична особа, що наділена повноваженнями та виконує у межах своєї компетенції специфічні завдання щодо виявлення, попередження та припинення нелегальної міграції. Зазначено, що до кола основних суб’єктів протидії нелегальній міграції в Україні входять такі органи, як Державна міграційна служба України, Державна прикордонна служба України, Національна поліція України, Служба безпеки України, місцеві суди, апеляційні суди, Верховний Суд, органи місцевого самоврядування та місцеві державні адміністрації, громадські організації та міжнародні інституції. Встановлено особливості їх адміністративно-правового статусу.

The article emphasizes that the subject of combating illegal migration in Ukraine is a natural or legal entity that is empowered and performs specifi c tasks within its competence to detect, prevent and stop illegal migration. It was determined that, from the point of view of legal interpretation, the system of subjects of combating illegal migration in Ukraine is an institutional structure that includes state bodies and institutions responsible for the implementation of state policy in the fi eld of migration, ensuring law and order at the state border. From the point of view of a functional interpretation, the system of entities for combating illegal migration in Ukraine is a complex of interrelated actions and measures carried out by authorized bodies and institutions aimed at preventing the entry of illegal migrants into the territory of Ukraine, their detection, detention and return to countries of origin From the point of view of socio-economic interpretation, the system of subjects of combating illegal migration in Ukraine is a set of individuals, public authorities, enterprises, institutions and organizations that direct their activities to support socio-economic stability in the country It has been established that the main subjects of combating illegal migration in Ukraine include such bodies as the State Migration Service of Ukraine, the State Border Service of Ukraine, the National Police of Ukraine, the Security Service of Ukraine, local courts, appeals courts, the Supreme Court, local self-government bodies and local state administrations, public organizations and international institutions.

Отмечено, что субъект противодействия нелегальной миграции в Украине - это физическое или юридическое лицо, наделенное полномочиями и выполняющее в пределах своей компетенции специфические задачи по выявлению, предупреждению и прекращению нелегальной миграции. В круг основных субъектов противодействия нелегальной миграции в Украине входят такие органы, как Государственная миграционная служба Украины, Государственная пограничная служба Украины, Национальная полиция Украины, Служба безопасности Украины, местные суды, апелляционные суды, Верховный Суд, органы местного самоуправления и местные государственные администрации, общественные организации и международные институты. Установлены особенности их административно-правового статуса.
The system of subjects against illegal migration in Ukraine and the peculiarities of their administrative and legal status
Keywords: адміністративно-правовий статус; система суб’єктів; адміністративно-правова протидія; нелегальна міграція; адміністративно-правове регулювання; публічне управління; адміністративне законодавство; administrative-legal status; system of subjects; administrative-legal counteraction; illegal migration; administrative-legal regulation; public administration; administrative legislation; административно-правовой статус; система субъектов; административно-правовое противодействие; нелегальная миграция; административно-правовое регулирование; публичное управление; административное законодательство